A Wild-plant extract could eliminate infectious-pathogens, Ranyah, KSA - Sherifa Mostafa M. Sabra (Journal of Biotechnology and Biomedical Science, 2023)
Saudi Arabia is rich in Juniperusprocera Hochst. ex Endl (Cupressaceae) as a medicinal plant. Its known as Arar, its present southwards, KSA. It's used as traditional medicine in the southwestern, KSA. The aim was according to
Keywords: Juniperus procera